Therapeutic targeting of leukemia stem cells in acute myeloid leukemia - Barbosa, Karina; Deshpande, Aniruddha J. (Frontiers in Oncology, 2023)
One of the distinguishing properties of hematopoietic stem cells is their ability to self-renew. Since self-renewal is important for the continuous replenishment of the hematopoietic stem cell pool, this property is often hijacked in blood cancers. Acute myeloid leukemia (AML) is believed to be arranged in a hierarchy, with self-renewing leukemia stem cells (LSCs) giving rise to the bulk tumor. Some of the earliest characterizations of LSCs were made in seminal studies that assessed the ability of prospectively isolated candidate AML stem cells to repopulate the entire heterogeneity of the tumor in mice. Further studies indicated that LSCs may be responsible for chemotherapy resistance and therefore act as a reservoir for secondary disease and leukemia relapse. In recent years, a number of studies have helped illuminate the complexity of clonality in bone marrow pathologies, including leukemias. Many features distinguishing LSCs from normal hematopoietic stem cells have been identified, and these studies have opened up diverse avenues for targeting LSCs, with an impact on the clinical management of AML patients. This review will discuss the role of self-renewal in AML and its implications, distinguishing characteristics between normal and leukemia stem cells, and opportunities for therapeutic targeting of AML LSCs.